2021
DOI: 10.22373/sjhk.v5i2.10570
|View full text |Cite
|
Sign up to set email alerts
|

Legal Policy of Child Marriage In the Covid-19 Pandemic Period

Abstract: The increase in marriage dispensation applications that occurred during the Covid-19 pandemic also caused the high number of child marriage. Nevertheless, this has been strictly required in Law Number 16 of 2019 concerning Amendments to Law Number 1 of 1974 concerning Marriage (Marital Law), the minimum age limit for men and women is 19 years, and requirements of irregularities for this age that must meet urgent criteria and sufficient support evidence. This is done, to reduce underage child marriages as a for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 0 publications
1
7
0
2
Order By: Relevance
“…The current study also found that up to 65% of the child marriage dispensation cases (absolute numbers) in this study were registered on Java Island as it is the most populated island. This finding was also observed before the pandemic where West Java showed the highest absolute numbers of child marriages in 2015 (Subchi, Arsadani, Helmi, & Faridho, 2021). The high number of child marriage dispensations might be associated with the numbers of COVID-19 cases in Java, where the highest positive case numbers were also recorded on this Island.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…The current study also found that up to 65% of the child marriage dispensation cases (absolute numbers) in this study were registered on Java Island as it is the most populated island. This finding was also observed before the pandemic where West Java showed the highest absolute numbers of child marriages in 2015 (Subchi, Arsadani, Helmi, & Faridho, 2021). The high number of child marriage dispensations might be associated with the numbers of COVID-19 cases in Java, where the highest positive case numbers were also recorded on this Island.…”
Section: Discussionsupporting
confidence: 63%
“…However, despite this comprehensive information, this study only analysed data from the Muslim population and could not provide specific information like the age of grooms and brides as well as the Judge's decisions/verdicts as this detailed information was not uploaded all to the Supreme Court's databases. One of the national media mass reported that 97% of the applications were granted with 60% of them involving children under 18 years old (Subchi et al, 2021). In addition, this quantitative study could also not be able to explain the process of the Judges' decisionmaking.…”
Section: Strengths and Limitationsmentioning
confidence: 85%
“…This study uses secondary data in the form of laws and regulations, literature books related to research material (Melinda & Djajaputra, 2021). The data obtained was then analyzed using a qualitative analysis method presented in the form of description (Subchi et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…The findings from Subchi et al (2021) revealed that the high number of child marriages during the COVID-19 pandemic was due to the granting of an early marriage dispensation request. In fact, strictly speaking the minimum age limit for men and women is 19 years which is regulated by Law Number 16 of 2019 concerning Amendments to Law Number 1 of 1974 concerning marriage.…”
Section: Child Marriagementioning
confidence: 99%